2012
DOI: 10.1063/1.3681594
|View full text |Cite
|
Sign up to set email alerts
|

Photonically enhanced flow boiling in a channel coated with carbon nanotubes

Abstract: High heat dissipation rates are enabled by multi-phase cooling schemes owing to latent heat uptake. We demonstrate enhanced flow boiling from a carbon nanotube (CNT)-coated copper surface exposed to low-intensity ultraviolet (UV)-visible excitation. Compared to non-illuminated results, the average boiling incipience temperature decreased by 4.6 C and heat transfer coefficients improved by 41.5% with light exposure. These improved results are attributed to augmented hydrophilicity upon exposure to UV light and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 23 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Similar results were obtained by Singh et al [65] with CNTs on silicon substrates. Recently, Kousalya et al [66] employed ultraviolet light on the CNT structures and reported an improvement in heat transfer performance with a 4.6 C reduction in the wall superheat at a heat flux of around 50 W/cm 2 . The ultraviolet light was utilized to make a CNT surface hydrophilic as originally reported by Takata et al [67].…”
Section: Nanostructuresmentioning
confidence: 99%
“…Similar results were obtained by Singh et al [65] with CNTs on silicon substrates. Recently, Kousalya et al [66] employed ultraviolet light on the CNT structures and reported an improvement in heat transfer performance with a 4.6 C reduction in the wall superheat at a heat flux of around 50 W/cm 2 . The ultraviolet light was utilized to make a CNT surface hydrophilic as originally reported by Takata et al [67].…”
Section: Nanostructuresmentioning
confidence: 99%
“…Further, while the hydrophilicity of NWs and CNTs with water has been reported in the literature [205,206], aligned arrays of nanotubes have also been shown to behave as superhydrophobic surfaces [207]. Hence, surfactants may be used for liquid conveying applications [208], or nanostructures may be functionalized for heat transfer applications via metallization [51], hydrochloric acid treatment [209], or ultraviolet excitation [210]. Nanostructures have a high number of pores per unit substrate area, and thereby may also offer an increase in the thin-film area for evaporation.…”
Section: Nanostructured Capillary Wicks For Vapor Chamber Applicationsmentioning
confidence: 99%
“…Artificial nucleation cavities were formed on the boiling surfaces to enhance nucleate boiling by various methods, such as micromachining [18][19][20][21], nanostructured surfaces [22][23][24][25][26], porous metal coating [27][28][29], and chemical etching [30,31]. Recently, nanowires (NWs) [32,33] and carbon nanotubes (CNTs) [34][35][36] were used to enhance nucleate pool boiling and convective boiling in microchannels [23,25,26,34,37,38] coefficient and critical heat flux were reported owing to the higher nucleation site density and enhanced wettability. However, optimization of surface properties to control bubble size, forces acting on bubble and flow patterns/ regimes has not yet been well resolved.…”
Section: Introductionmentioning
confidence: 99%